Agency and the Metaphysics of Nature. Issue 2 (3rd April 2018) - Sims, Andrew
Abstract: Gallagher poses a phenomenologically-inspired challenge to a classical metaphysics of nature which is associated with contemporary natural sciences. This metaphysics can be reconstructed in terms of two distinct commitments: reductionism and individualism. This comment on Gallagher's [2019 ] article attempts to show how a revision of the classical metaphysics can be made intelligible in light of those two commitments. It requires a strong interpretation of the ecological framework for understanding cognition. Such a revision would give agency a central place in the revised metaphysics of nature.